Case Report: A Rare Case of a Combination of Omphalocele With Umbilical Teratoma - Bilal, Ruslan; Rustemov, Dastan; Sakuov, Zhenis; Ibraimov, Bahytkaly; Kozhakhmetov, Arman (Frontiers in Pediatrics, 2021)
Omphalocele is a congenital malformation of the abdominal wall, which occurs with a frequency of 1-5000 newborns. The prognosis of treatment often depends on the presence of concomitant malformations. The most common contents of the hernia with omphalocele are the intestinal loops, liver, spleen. However all organs of the abdominal cavity can be part of the hernial sac with large sizes of omphalocele. In this article, we describe a rare case of a combination of an omphalocele with a mature teratoma and report the successful single step surgical treatment. On the first day after birth, a simultaneous operation - Removal of teratoma with abdominoplasty was performed. The postoperative period was uneventful, and the child was discharged for recovery.